Isolation and characterization of the oil bodies and oleosin of coconut (Cocos nucifera L.) - Rodelas, Abigail Joy D. (Animo Repository, 2008)
Oil bodies were isolated from the solid endosperm of 11–12 month old coconut and purified by sucrose density gradient washing, urea washing and floatation centrifugation. Under light microscope, purified oil bodies showed two types of small and large oil bodies: about 90% with diameter of 0.5–4.0 μ μm and 10%, 10–40 m, respectively. The oil bodies consisted of 97% triacylglycerols, phospholipids (phosphatidylethanoloamine and phosphatidylcholine) and the oil body storage protein oleosin. Puri- fied oleosin showed one band of 14400 on SDS-PAGE. Two-dimensional electrophoresis resolved one band of 14400 with an isoelectric pH between 9 and 10. The 14400 band had an N-terminal amino acid sequence of GEERR or GEEER. Additional urea washings of the coconut oil bodies followed by ether delipidation revealed two oleosin bands of 14400 and 11000 Mr on SDS-PAGE.